HUBUNGAN PERSEPSI MASYARAKAT DENGAN PERILAKU SWAMEDIKASI PROFILAKSIS COVID-19 DENGAN (PENDEKATAN HEALTH BELIEF MODEL) - Paudi, Cindy Amalia Octaviani; Syamsi, Nur; Nayoan, Christin Rony; Tanra, Andi Alfia Muthmainnah (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2023)
Introduction: Self-medication or self-medication is a community effort to treat self-diagnosed disorders without consulting a medical practitioner or medical supervision. HBM is used to explain the concept of understanding individual behavior. The behavior in question is health behavior, both in the realm of preventive and curative. Purpose: To determine whether there is a relationship between people's perceptions of COVID-19 prophylactic self-medication behavior with the theory of the health belief model. Methods: The type of research used in this research is an observational study using a cross-sectional design. By distributing questionnaires via Google form. Results: based on the results of the analysis using the Spearman rho correlation test obtained perceived vulnerability (p=0.000 r=-0.491), perceived seriousness (p=0.000, r=-0.477), perceived benefits (p=0.000, r=-0.415), perceived barriers (p=0.000, r=-0.392), perceptions of cues to action (p=0.000, r=-0.392), perceptions of self-efficacy (p=0.000, r=-0.543) Conclusion: There is a relationship between people's perceptions of Covid-19 prophylactic self-medication behavior and the health belief model theory, there is a relationship between perceived vulnerability, perceived seriousness, perceived benefits, perceived obstacles, cues to action and self-efficacy, and self-medication behavior.